2014
DOI: 10.1109/tmag.2014.2326959
|View full text |Cite
|
Sign up to set email alerts
|

Improved Magnetic Tunnel Junctions Design for the Detection of Superficial Defects by Eddy Currents Testing

Abstract: In the last decade, magnetoresistive sensors attracted great interest for integration in eddy current-based non-destructive testing due to their high sensitivity and signal to noise ratio in a large range of frequencies (from dc to hundreds of megahertz). In this paper, a sensor composed of several magnetic tunnel junction (MTJ) elements in series is optimized and included in a custom probe configuration for the detection of superficial defects. Since the signal magnetic fields are very low, a finite element m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Major improvements were achieved upon the inclusion of crystalline MgO barriers and textured MTJ stacks. TMR values up to ∼600% were reported at room temperature for simple CoFeB/ MgO/CoFeB structures [38], and optimum values decrease to ∼250% for complex engineered stacks developed for device applications [9,[39][40][41][42]. The reported high TMR values are a consequence of coherent spin polarized tunneling.…”
Section: Tunnel Magnetoresistancementioning
confidence: 94%
“…Major improvements were achieved upon the inclusion of crystalline MgO barriers and textured MTJ stacks. TMR values up to ∼600% were reported at room temperature for simple CoFeB/ MgO/CoFeB structures [38], and optimum values decrease to ∼250% for complex engineered stacks developed for device applications [9,[39][40][41][42]. The reported high TMR values are a consequence of coherent spin polarized tunneling.…”
Section: Tunnel Magnetoresistancementioning
confidence: 94%
“…120 A biorthogonal rectangular probe was developed by Zhang et al 52 Simulation results showed the new biorthogonal rectangular probe has a lesser effect on the lift-off with higher sensitivity detection. Meanwhile, Cardoso et al 121 optimized the sensor configuration in the eddy current probe design. A finite element modeling simulation was used to measure the accuracy detection of the probe design.…”
Section: Optimization Of Ect Probes Designmentioning
confidence: 99%
“…This study was done with two different sensors configuration and their validation was done by experimental and analytical studies of a CoCrPt thin film patterned array. 7 Two different sensors were used: 1) Sensor #1 (S1) composed of 72 MTJs structures with a single area of 50x50 µm 2 , connected in series and disposed in a 9x8 matrix (500x500 µm 2 ) to maximize the signal to noise ratio (SNR); 8 2) Sensor #2 (S2) consists on one line of 4 MTJs with single area of 10x4 µm 2 , connected in series with in a total spatial area of 59x4 µm 2 , which is expected to have more accuracy on the reading distance (RD); a schematic drawing of both sensors configuration are presented in Figure 1(a). After processing, an optimized sequence of two consecutive annealing steps at different temperatures for each AFM layer (each IrMn has different blocking temperature due to the different thicknesses) were performed to set the free layer perpendicularly to the pinned layer and achieve a linear response.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%